Educação inclusiva: significados e sentidos configurados a partir de uma experiência formativa docente - Rodrigues, Paloma Roberta Euzébio (2017)
The promulgation of inclusive, public policies which deliberated more access to the regular educational institutions for those students with special needs, who used to be excluded from these spaces, aims to debate the teaching practice and formation. In this perspective, this research, based on Vygotsky’s Cultural Historic Psychology, aimed to show the objective and implicit conditions of teaching practice concerning demands and propositions of inclusive education. In order to reach it, our main objective was to analyse the meanings set along the inclusive education process by basic education teachers who deal with students with special needs. Aiming to identify the meanings the inclusive education presents, we invited 10 teachers to be part of this research. They were working in one basic, public school from Campo Belo, Minas Gerais. We adopted the qualitative approach as an intervention tool. We used different data collector resources to build the information we needed: characterization questionnaire; mediator materials, such as image, video, songs, text, all of which presented in group dynamics; and the study diary, in which all the information was transcripted and organized. Those different instruments brought some questions to light concerning the conception of teaching formation, comprehension of inclusive policies purposes, understanding of the special needs the students might have during the inclusive process, the representation of the scholar inclusive process and the teaching perspectives for the effectiveness of inclusion. The gathered information was analysed qualitatively in a constructive-interpretative manner, starting at two meaning standpoints: 1) From the representation to the construction of the basic school in an inclusive education perspective; and 2) Inclusive Education: from the objectification to the subjectification of attitudes. From the analysis of these two meaning groups, we were able to notice that the meaning teachers share is based on the families lack of understanding about the teacher’s educational role in basic school and the incoherence of educational, political assumptions and realities faced by the teachers. Both meanings deflagrate interpretations which impair the effectiveness of inclusive education: withdrawal, isolation, frustration, professional downgrading, helplessness, public policies disapproval, disrespect or, even, overvalued workplace feelings. Finally, we came to the conclusion that it is highly importat that continuous education and practices which qualify teachers to elaborate effective strategies take place, so that families could embrace more their kids’ educational process. This would help promote healthy professional and collaborative relations, both inside and outside the teaching context. We believe that a proper space for debating the teaching practice at school contributes to the inclusion of teachers in their educational institution, which leads to the each time less solitary work they perform.